Children Learning in Science Model and Critical Thinking Skills of Grade IV Students: Model Pembelajaran Sains dan Keterampilan Berpikir Kritis Siswa Kelas IV - Arieshandy, Risca Ayu; Rintayati, Peduk; Triyanto, Triyanto (Universitas Muhammadiyah Sidoarjo, 2025)
General background: Critical thinking is a fundamental competency in 21st-century education and is emphasized in Indonesia’s Kurikulum Merdeka. However, learning in science and social studies (IPAS) at the elementary level often remains teacher-centered, limiting students’ higher-order thinking. Specific background: The Children Learning in Science (CLIS) model, grounded in constructivist principles, offers an alternative by engaging students’ prior knowledge, encouraging exploration, and fostering collaborative learning. Knowledge gap: Previous studies have highlighted CLIS’s benefits for creativity and learning outcomes, but few have examined its effectiveness in developing critical thinking skills while considering the moderating role of learning motivation. Aims: This study investigates the effectiveness of CLIS compared to Direct Instruction (DI) in enhancing critical thinking among Grade IV students in Kedawung District, with attention to variations in learning motivation. Results: Using a quasi-experimental pretest–posttest control group design with ANOVA analysis, findings show CLIS significantly outperforms DI, with higher post-test means and consistent effects across high, medium, and low motivation groups, and a significant interaction between learning model and motivation. Novelty: The study integrates motivation as a moderating factor in evaluating CLIS effectiveness, offering a more comprehensive perspective. Implications: The results support CLIS as a strategic model to strengthen critical thinking in elementary science education and provide practical insights for teachers and policymakers in implementing student-centered learning. Highlights: CLIS significantly improves critical thinking compared to Direct Instruction. Learning motivation interacts with CLIS but shows consistent positive outcomes. Findings provide practical insights for teachers and policymakers. Keywords: CLIS, Critical Thinking, Learning Motivation, Elementary Education, Science Learning